Legal Protection of Outsourced Workers on Outsourcing Agreements with Pt. X in Sidoarjo - Benita Dita Rezanti; Ghanisworo Ayu Pratiwi; Athifatul Wafirah; Satiti Hanifah; Sella Flatinaningtyas Ayu Lestari (IHSA Institute, 2022)
The focus of the problem is divided into (1) analysis of the legal relationship of the parties in the outsourcing agreement Company X in Sidoarjo City, (2) legal protection of workers in outsourcing agreement Company X in the city of Sidoarjo. This study uses type of normative juridical research, based on analysis of legal facts, supported by legal literature and legislation as empirical data. The results of this study are (1) legal relations focusing on worker and also Company X, because they have agreed in the work Agreement and become a strong legal basis and must be obeyed by both parties, Company Y can not be sued because the company is only a labor user company only. (2) legal protection for outscourcing workers can be done preventively with legal protection set by goverment, because there has been dispute over rights in indrustrial relations. So repressive legal protection is more appropriate to be applied by fighting for the normative rights of outsourcing workers through non-litigation and litigation, this issue raised by this author finally completed through mediation from Sidoarjo City Disnaker with an agreement of Company X will pay compensation for the remaining wages as contained in the employment agreement.